FORMATION OF A PROFESSIONAL ORIENTATION OF THE FUTURE TEACHER DURING THE ORGANIZATION OF EDUCATIONAL PROCESS AT PEDAGOGICAL UNIVERSITY - М.V. Viktorova (Academy of Cognitive and Natural Sciences, 2022)
The article deals with significance of pedagogical focus as an important component of future teachers ' professional and pedagogical training